Proceedings International Conference on Dependable Systems and Networks
DOI: 10.1109/dsn.2001.941418
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of non-specification-based approaches to logic testing for software

Abstract: Testing is a crucial part of the developnient of highly dependable systems. In this paper we consider testing of an implementation that is intended to satisfy a boolean forniula. I n the literature, specification-based testing has been suggested f o r this purpose. Typically, such methods first hypothesize a fault class and then generate tests. However there is alniost no research that justifies fault classes proposed previously. Moreover specifications amenable to autoiiiutic test generation are not always av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Type of Experiment Constraints Included? CT / RT ART / RT CT / ART [8], [9], [10], [11], [12], [13], [14], [15], [16] Case Analysis No √ [17], [18], [19] Simulation No √ [20], [21] Empirical Study Yes √ [5] Formal Analysis No √ [22] Simulation No √ [23], [24], [25], [26] Empirical Study No √ [27] Simulation Yes √ [28] Simulation No √ √ √ both theoretically and empirically [22], [23], [24], [25], [26]. However, these studies assumed no constraints between parameters, which may be problematic as real-world applications often have constrained domains [29], [30].…”
Section: Referencementioning
confidence: 99%
See 2 more Smart Citations
“…Type of Experiment Constraints Included? CT / RT ART / RT CT / ART [8], [9], [10], [11], [12], [13], [14], [15], [16] Case Analysis No √ [17], [18], [19] Simulation No √ [20], [21] Empirical Study Yes √ [5] Formal Analysis No √ [22] Simulation No √ [23], [24], [25], [26] Empirical Study No √ [27] Simulation Yes √ [28] Simulation No √ √ √ both theoretically and empirically [22], [23], [24], [25], [26]. However, these studies assumed no constraints between parameters, which may be problematic as real-world applications often have constrained domains [29], [30].…”
Section: Referencementioning
confidence: 99%
“…Bell and Vouk [10] compared 2-way and random testing for detecting security faults on two network related products, and Pretschner et al [11] compared them for testing access control policies on four cases. Both studies showed the superiority of 2-way CT. Additionally, Kobayashi et al [9] applied τ -way and random testing to examine logical expressions from the specification of TCAS II. Their work was further expanded by Ballance et al [17] and Vilkomir et al [18], where automatically generated expressions were used for simulation.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation